2016
DOI: 10.1080/17461391.2016.1236840
|View full text |Cite
|
Sign up to set email alerts
|

Force– and power–time curve comparison during jumping between strength‐matched male and female basketball players

Abstract: The purpose of this study was to compare force- and power-time curve variables during jumping between Division I strength-matched male and female basketball athletes. Males (n = 8) and females (n = 8) were strength matched by testing a one-repetition maximum (1RM) back squat. 1RM back squat values were normalised to body mass in order to demonstrate that strength differences were a function of body mass alone. Subjects performed three countermovement jumps (CMJ) at maximal effort. Absolute and relative force- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 36 publications
9
66
4
Order By: Relevance
“…The most important consideration here is that a consistent approach to BW determination is applied to enable fairer data comparisons between trials, sessions and athletes. The reason for the suggested weighing duration of 1 second is largely a consequence of a study conducted by Street et al (28) which showed that weighing durations of ≥ 1 second leads to a ≤ 1% overestimation of JH (calculated based on the impulse-momentum relationship) when compared to the maximum weighing duration of 2 seconds (29). A ≤ 1% overestimation of JH is considered acceptable (22,28), thus we recommend that the weighing phase should last for ≥ 1 second.…”
Section: Weighing Phasementioning
confidence: 92%
See 4 more Smart Citations
“…The most important consideration here is that a consistent approach to BW determination is applied to enable fairer data comparisons between trials, sessions and athletes. The reason for the suggested weighing duration of 1 second is largely a consequence of a study conducted by Street et al (28) which showed that weighing durations of ≥ 1 second leads to a ≤ 1% overestimation of JH (calculated based on the impulse-momentum relationship) when compared to the maximum weighing duration of 2 seconds (29). A ≤ 1% overestimation of JH is considered acceptable (22,28), thus we recommend that the weighing phase should last for ≥ 1 second.…”
Section: Weighing Phasementioning
confidence: 92%
“…The reason for the suggested weighing duration of 1 second is largely a consequence of a study conducted by Street et al (28) which showed that weighing durations of ≥ 1 second leads to a ≤ 1% overestimation of JH (calculated based on the impulse-momentum relationship) when compared to the maximum weighing duration of 2 seconds (29). A ≤ 1% overestimation of JH is considered acceptable (22,28), thus we recommend that the weighing phase should last for ≥ 1 second. It is essential, however, that the athlete remains stood upright and as still as possible during the weighing phase as it is vital that center of mass (COM) velocity and displacement equal zero at the onset of movement for the numerical integration method to be accurate (29).…”
Section: Weighing Phasementioning
confidence: 92%
See 3 more Smart Citations